The Interiors of the Mansions of Architect Carl Schmidt. The Range of Styles - Dolgova, Anastasia I. (Actual Problems of Theory and History of Art, 2014)
The paper focuses on the interiors of four houses built by Carl Schmidt in St. Petersburg and its suburbs: the V.V. Tis city residence, the P.P. Forostovskii city residence, the house in Pavlovsk built by the architect for his own family and the O.V. Palei palace in Pushkin. These monuments cover all the periods of the architect’s work and refl ect the changes that took place in the architecture of this time in general and in the interior decoration of St. Petersburg mansions in particular. Comprehensive examination of these buildings interiors helps us to form a holistic view on the development of the interior art in St. Petersburg city residences. The study is based on the in-situ observations, photos and archive materials. The article presents a whole range of styles that can be seen in the interiors of C. Schmidt city residences and dachas. Firstly — delicate inclusion of the «new style» elements in the eclectic interiors, then — the prevalence of the Art Nouveau details with the preserving of some details of the historical styles, further — the stylistic unity of some summer residences and mansions (also including the special genre of the architecture — architect’s own house) and, fi nally, the plume of Art Nouveau — using of some of its methods and the individual elements in the interiors of neoclassicism.
Keywords: architect C. Schmidt; city residences and dachas; St. Petersburg Art Nouveau; neoclassicism; V.V. Tis city residence; P.P. Forostovskii city residence; C. Schmidt house; Palei palace